Efficacy of Ventriculoperitoneal Shunt for Postoperative Central Nervous System Infection Complicated with Hydrocephalus - Chen, FuMei; Wang, Na; Wang, Li; He, ZhiYang; Xu, KangLi; Zhan, TianXiang; Zhou, Qian; Wang, Hao; Yang, XiaoFeng (Asian Journal of Neurosurgery, 2024)
Objective Our aim was to assess the efficacy of ventriculoperitoneal shunt (VPS) for treating postoperative central nervous system infection (PCNSI) complicated with hydrocephalus and to identify factors associated with treatment failure.Materials and Methods We conducted a retrospective analysis of PCNSI patients with hydrocephalus treated by VPS at the Department of Neurosurgery, the First Affiliated Hospital, College of Medicine, Zhejiang University, between December 2012 and January 2020. Functional recovery was evaluated during follow-up using the Glasgow Outcome Scale.Results A total of 29 patients (21 males, 8 females) were enrolled in the study (mean age: 56.4 ± 12.0 years, range: 18.0–77.0 years). Seventeen patients were treated successfully by VPS (58.6%). Among the 11 patients with shunt complications (37.9%), 8 (27.6%) presented with fever, 3 (10.3%) with shunt infection, and 3 (10.3%) with shunt obstruction. Univariate analysis identified low Glasgow Coma Scale (GCS) score (3–8) at the time of VPS and post-treatment fever as predictive of shunt failure.Conclusion VPS was effective for treating PCNSI complicated with hydrocephalus. However, patients with low GCS score at the time of VPS or fever post-treatment were at greater risk of shunt failure and poor outcome.
Keywords: ventriculoperitoneal shunt; postoperative central nervous system infection; hydrocephalus